2019
DOI: 10.1038/s41598-019-52604-9
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Burkholderia cenocepacia cell wall morphology and mechanical properties during cystic fibrosis lung infection, assessed by atomic force microscopy

Abstract: The influence that Burkholderia cenocepacia adaptive evolution during long-term infection in cystic fibrosis (CF) patients has on cell wall morphology and mechanical properties is poorly understood despite their crucial role in cell physiology, persistent infection and pathogenesis. Cell wall morphology and physical properties of three B. cenocepacia isolates collected from a CF patient over a period of 3.5 years were compared using atomic force microscopy (AFM). These serial clonal variants include the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Cell stiffness has been described to be strongly affected by the actin filamentous structures under the cell membrane [21]. In recent years, force microscopy has unveiled the relevance of these nanomechanical properties in important cellular mechanisms, such as migration/locomotion [22], differentiation [23] or as a marker for disease progression [24,25]. It has become evident that these properties are fundamental to explain cell's structure, evolution, and response to different stimuli, making AFM a potential tool for biomedical diagnosis and prognosis, with very promising results already obtained in the areas of cancer [26] or cardiovascular diseases [27].…”
Section: Discussionmentioning
confidence: 99%
“…Cell stiffness has been described to be strongly affected by the actin filamentous structures under the cell membrane [21]. In recent years, force microscopy has unveiled the relevance of these nanomechanical properties in important cellular mechanisms, such as migration/locomotion [22], differentiation [23] or as a marker for disease progression [24,25]. It has become evident that these properties are fundamental to explain cell's structure, evolution, and response to different stimuli, making AFM a potential tool for biomedical diagnosis and prognosis, with very promising results already obtained in the areas of cancer [26] or cardiovascular diseases [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that the OAg absence leads to increased internalization of B. cenocepacia into macrophages upon phagocytosis Kotrange et al, 2011) and to facilitate B. multivorans growth inside macrophages (Schmerk and Valvano, 2013). Moreover, the OAg presence was found to interfere with the adhesion of B. cenocepacia to bronchial epithelial cells although it was reported to increase the ability of B. cenocepacia to adhere to atomic force microscope Si 3 N 4 tip (Hassan et al, 2019b). Collectively, the loss of the OAg seems advantageous for disease development associated with B. cenocepacia or B. multivorans infections.…”
Section: Discussionmentioning
confidence: 99%
“…A model proposed for Escherichia coli suggests that the flux of nutrients into the cell controls the synthesis of fatty acids which, in turn, controls cell size through modeling of the cell membrane surface area and cytoplasmic volume (Yao et al, 2012 ). A recent study performed in our lab also demonstrated a clear length and height decrease of B. cenocepacia cells during more than 3 years of chronic infection, suggesting that the population converged evolutionarily toward the minimization of bacterial size (Hassan et al, 2019 ). Small microbial cell size might allow evasion from important host defenses and cell shape itself has been suggested as a virulence trait (Vadia et al, 2017 ).…”
Section: Discussionmentioning
confidence: 63%